Persian version of brief infant sleep questionnaire (BISQ): a psychometric evaluation - Maryam Yazdi; Maryam Bemanalizadeh; Roya Kelishadi (BMC Pediatrics, 2024)
Abstract Background The high prevalence of sleep problems and their negative consequences on children and parents highlight the need to design early screening instruments to evaluate sleep problems in early childhood. We aimed to determine the validity and reliability of the Brief Infant Sleep Questionnaire (BISQ) among the Iranian population. Methods and materials This study included 646 one-year-old infants by random sampling from the PERSIAN birth cohort study. Following the forward-backward translation of the BISQ, its psychometric properties, including construct validity in terms of concurrent and convergent validities as well as reliability, were evaluated. Results The CVIs and CVR ranged between 0.8 and 1.00 for all items. Therefore, we keep all the items of the original version of the BISQ in the Persian BISQ. Concurrent validity was assessed by comparing items of the Persian BISQ among different maternal views regarding their infant’s sleep. All BISQ items were significantly different among the two levels of maternal view about the infant’s sleep problem except daytime sleep duration. The convergent validity of the BISQ was evaluated by calculating the correlation between BISQ items and the ISQ (infant sleep questionnaire) total score as a similar tool. ISQ score was adequately correlated with nocturnal sleep latency and the number of waking at night (rs ranged from 0.59 to 0.72). In addition, the associations of mothers’ and infants’ demographic variables and nutritional and gestational variables with BISQ items were presented to confirm construct validity. Strong correlations were found between the repeated sleep measures for sleep arrangement, sleep position, and sleep situation (kappa ranged from 0.65 to 0.84), nocturnal sleep duration, daytime sleep duration number of wakings at night, night waking duration, nocturnal sleep latency and sleep-onset time (ICC ranged 0.91 to 0.99). Conclusion The Persian version of the BISQ is a reliable and valid measure for assessing sleep problems in infants. It would be helpful to be utilized for the early diagnosis of infants’ sleep problems.